An Analysis and Design of Simulation Modelling for Airplane Passenger Boarding Strategy during Normal and New Normal Periods (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Boarding process is the main activity that became the key efficiency in each turnaround process on the airport. Thesuccessful in achieving time efficiency will give some benefit to all parties, including airlines, airport management andpassengers, especially related to business sustainability, operational and customer satisfaction reasons. The objective of theresearch is to design an effective model for passenger boarding strategy that focus on airplane with a 180-seat configuration, inscenarios for both normal and new normal periods using agent-based simulation in NetLogo 6.1.1. The simulation output wasprocessed using descriptive and sensitivity analysis and also Chi Square test of independence methods. The simulation resultsshow that Wave strategy which is implemented through the seat-assignment and group-assignment has successfullydemonstrated its effectiveness and gives an alternative to be applied by the airlines, for both in normal and new normal periods.By comparing the average boarding time with scenarios in the normal period (load factor 100%) and the new normal period(load factor 66.7%), it is found that the average boarding time by applying 1.0 meter of social distancing is about 78.21%,while for 1.5 meters about 116.06% and for 2.0 meters about 138.29%. Furthermore, by using the Chi Square test ofindependence analysis, it can be seen that the application of social distancing is highly correlated to the effectiveness boardingstrategy.